Network Oncolgy Specialist Advisory Service – A Survey of the Psychosocial Situation of Long Term Cancer Survivors During Childhood or Adolescents - Toenne, Rebecca; Baumeister, Rebecca; Koch, Anika; Lindhorst, Kristin; Reinhardt, Dirk; Kremeike, Kerstin (Klinische Pädiatrie, 2021)
Background The number of long term cancer survivors during childhood or adolescence is increasing steadily. Survivors often suffer from physical or psychosocial long term effects. There is currently little data on the arrangement of long term aftercare in the field of psychosocial care.Methods In November 2017 a questionnaire was sent to 1900 cancer survivors aged between 18 and 35 years whose diagnosis dated at least five years prior. The obtained data serve as a condition and needs assessment, how the (psychosocial) long-term aftercare is perceived by the survivors and what else is desired. The analysis was conducted using descriptive statistics as well as the calculation of bivariate correlations.Results The response rate was 54.9% (n=1.043). The median interval from the first diagnosis was 20 years. In total 666 survivors (63.9%) stated that they suffered from at least one long term effect. Within this, especially neurocognitive themes played a role. 87.2% of the respondents had the feeling that they had overcome the illness/therapy well.Conclusion Through a stronger patient-focussed orientation concerning the current care and advisory services, the situation of long term survivors could be improved. This especially includes access to relevant information that focuses on the available psychosocial and welfare services, as well as to advisory and care services. Additionally, the development and expansion of care structures in the areas of neurocognition and psychotherapy is important to ensure long term participation attendance.Hintergrund Die Zahl der Langzeitüberlebenden nach einer Krebserkrankung im Kindes- oder Jugendalter (Survivor) steigt stetig. Survivor leiden nicht selten unter körperlichen oder psychosozialen Spätfolgen. Für die Gestaltung der Langzeitnachsorge im Bereich der psychosozialen Versorgung liegen bislang kaum Daten vor.Methode 11/2017 wurde deutschlandweit ein Fragebogen an 1.900 Survivor im Alter von 18 bis 35 Jahren versandt, deren Erstdiagnose zum Befragungszeitpunkt mindestens fünf Jahre zurücklag. Die erhobenen Daten dienen als Zustands- und Bedarfserhebung, wie die (psychosozialen) Langzeitnachsorge von den Survivorn wahrgenommen und was darüber hinaus gewünscht wird. Die Auswertung erfolgte mittels deskriptiver Statistik sowie der Berechnung bivariater Korrelationen.Ergebnisse Der Rücklauf betrug 54,9% (n=1.043). Der mediane Abstand zur Erst-Diagnose betrug 20 Jahre. Insgesamt gaben 666 Survivor (63,9%) an, mindestens eines der abgefragten Items/Symptome bei sich zu beobachten. Hierbei spielen besonders neurokognitive Themen eine Rolle. Viele Angebote der Langzeitnachsorge sind den Survivorn nicht bekannt. 87,2% der Befragten haben das Gefühl, die Erkrankung/Therapie gut gemeistert zu haben.Schlussfolgerung Eine stärkere patientenorientierte Ausrichtung der derzeitigen Versorgungs- und Beratungsangebote könnte die Situation von Langzeitüberlebenden noch verbessern. Zentral sind hierbei der Zugang zu gezielten Informationen, eine psychosoziale und sozialrechtliche Betreuung sowie der Zugang zu Beratungs- und Versorgungsangeboten. Auch der Auf- und Ausbau von Versorgungsstrukturen im Bereich der Neurokognition und Psychotherapie ist für die langfristige Sicherstellung von Partizipation wünschenswert.
Keywords: cancerous disease; childhood and adolescence; long term aftercare; psychosocial care